2017
DOI: 10.1002/14651858.cd004956.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates for Paget's disease of bone in adults

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 70 publications
0
50
0
4
Order By: Relevance
“…In a recent Cochrane review, (66) no statistically significant difference was found in adverse effects with oral bisphosphonates compared with placebo (6 studies, 678 participants, risk…”
Section: Adverse Eventsmentioning
confidence: 96%
See 3 more Smart Citations
“…In a recent Cochrane review, (66) no statistically significant difference was found in adverse effects with oral bisphosphonates compared with placebo (6 studies, 678 participants, risk…”
Section: Adverse Eventsmentioning
confidence: 96%
“…When the data were expressed as the proportion of patients whose SF36 physical summary score improved after treatment, the difference favored zoledronic acid (RR ¼ 1.30, 95% CI 1.18-1.42). (66) In an extension of the same study, (100) the mean change from baseline SF36 summary score favored zoledronic acid (mean difference 3.8, 95% CI 3.12-4.49). However, this analysis was not intention to treat, and was based on a selected group of patients who had normal total ALP values at the end of the core study.…”
Section: Quality Of Evidence Very Low Patient Values and Preferencesmentioning
confidence: 98%
See 2 more Smart Citations
“…2 Since 1973, the pharmacological treatment of PDB contemplates the use of potent bisphosphonates that act by suppressing the excessive bone turnover from active disease to physiological range. 3,4 Genetically, PDB exhibits an autosomal dominant pattern of inheritance with incomplete penetrance. 5 To date, 28 different mutations in the SQSTM1 gene have been identified in 35% and 10% of individuals with familial and sporadic PDB, respectively, with the c.1215C>T, p.Pro392Leu mutation as the most common one.…”
Section: Introductionmentioning
confidence: 99%